Effects of buzzy device and distraction cards on pain relief during intravenous cannulation in children: A Randomized Controlled Trial - Mohammed Attaallah Ahmed; Al-Musawi Khatam M (Journal of Research Development in Nursing and Midwifery)
Background: Under ethical and legal professional obligations, nurses are required to utilize evidence-based methods to enhance the experience of children during intravenous cannulation. Non-pharmacological pain management techniques are increasingly employed in clinical settings, as they can be implemented without incurring additional costs or requiring extra time. The aim of this randomized controlled trial is to evaluate the effectiveness of a Buzzy device and distraction cards in reducing pain associated with peripheral intravenous catheter (PIVC) insertion among school-aged children. Methods: A randomized controlled trial study was conducted on 221 school-age children patients who underwent PIVC in emergency departments. Three groups of patients were randomly assigned using a lottery method: the Buzzy device group (n=73), the distraction cards group (n=71), and the control group (n=77) receiving the standard procedure without any interventions. The children were asked to evaluate the pain level immediately following PIVC using the Wong-Baker Faces Pain Scale. Using SPSS (version 26), the independent t-test, Fisher's exact test, analysis of variance, and chi-square test were used to analyze the data. Results: Children in the intervention groups experienced significantly less pain during the PIVC procedure compared to those in the control group, with a pain score of 5.45 ± 1.67 (p = 0.0001). There was no statistically significant difference in pain reduction between the two intervention methods: the distraction cards (2.54 ± 1.37) and the Buzzy device (2.43 ± 1.60), both showing effectiveness (p = 0.0001). Conclusion: The results of this study indicate that both the Buzzy device and distraction cards effectively reduce pain levels during intravenous cannulation when compared to the control group. Furthermore, the two strategies demonstrated equivalent effectiveness in pain reduction, as their outcomes were nearly identical. Therefore, it is recommended that these therapeutic approaches be employed to manage and alleviate pain associated with PIVC.